Use of Glomerular Filtration Rate Estimating Equations for Drug Dosing in HIV-Positive Patients. Issue 6 (August 2013) - Okparavero, Aghogho A; Tighiouart, Hocine; Krishnasami, Zipporah; Wyatt, Christina M; Graham, Hiba; Hellinger, James; Inker, Lesley A
Background: Current HIV treatment guidelines recommend using the Cockcroft–Gault equation for drug dosing adjustments. The use of newer glomerular filtration rate (GFR) estimating equations for drug dosing and the appropriateness of physician antiretroviral dosing based on estimated kidney function have not been studied in an HIV-positive population. Methods: We evaluated concordance between measured and estimated GFR for the assignment of kidney function categories designated by the US Food and Drug Administration (FDA) Guidance for industry for pharmacokinetic studies, and appropriateness of physician antiretroviral drug dosing for level of kidney function in 200 HIV-positive patients on stable antiretroviral therapy. Estimated kidney function was determined using the Chronic Kidney Disease-Epidemiology collaboration (CKD-EPI), Modification of Diet in Renal Disease (MDRD) Study and Cockcroft–Gault equations. Results: For assignment of FDA-designated kidney function categories, concordance rates between measured and estimated GFR using the CKD-EPI, MDRD Study and Cockcroft–Gault equations were 79%, 71% and 77%, respectively. This pattern was consistent across most subgroups. When actual prescribed dosages were compared with recommended dosages based on the level of estimated kidney function, 3–19% of study participants were prescribed higher than recommended dosages. The largest discordance between prescribed and recommended dosages was observed for the Cockcroft–Gault equation. Conclusions: The CKD-EPI equation has the highest concordance with measured GFR for the assignment of FDA-designated kidney function categories. Its use may lead to lower dosing-related errors in HIV-infected US adults on stable antiretroviral therapy. More education is required with respect to dose adjustment for level of kidney function.